A murine model of Trypanosoma brucei-induced myocarditis and cardiac dysfunction - Nathan P. Crilly; Marcelle Dina Zita; Alexander K. Beaver; Polina Sysa-Shah; Aashik Bhalodia; Kathy Gabrielson; Luigi Adamo; Monica R. Mugnier (Microbiology Spectrum)
ABSTRACT Trypanosoma brucei is a protozoan parasite that causes human and animal African trypanosomiases (HAT and AAT). Cardiac symptoms are commonly reported in HAT patients, and intracardiac parasites with accompanying myocarditis have been observed in both natural hosts and animal models of T. brucei infection. Despite the importance of T. brucei as a cause of cardiac dysfunction and the dramatic socioeconomic impact of African trypanosomiases in sub-Saharan Africa, there are currently no reproducible murine models of T. brucei-associated cardiomyopathy. We present the first clinically relevant, reproducible murine model of cardiac dysfunction in chronic T. brucei infection. Similar to humans, mice showed histological evidence of myocarditis and elevation of serum NT-proBNP with electrocardiographic abnormalities. Serum NT-proBNP levels were elevated prior to the development of severe ventricular dysfunction. On flow cytometry, myocarditis was associated with an increase of most myocardial immune cell populations, including multiple T cell and macrophage subsets, corroborating the notion that T. brucei-associated cardiac damage is an immune-mediated event. This novel mouse model represents a powerful and practical tool to investigate the pathogenesis of T. brucei-mediated heart damage and supports the development of therapeutic options for T. brucei-associated cardiac disease. In characterizing this model, we provide evidence that T. brucei causes cardiac disease, and we suggest that immunopathology is an important contributor to cardiac pathology. Along with other recent studies, our work demonstrates the importance of extravascular spaces, including the heart, for T. brucei pathogenesis.IMPORTANCEAfrican trypanosomiasis is a neglected tropical disease affecting both people and cattle, which represents a major public health problem in sub-Saharan Africa with an enormous socioeconomic impact. Cardiac disease represents an underappreciated clinical manifestation of African trypanosomiasis that may lead to lifelong illness despite successful treatment of infection. However, this aspect of African trypanosomiasis remains poorly understood, partially due to a lack of well-characterized and practical animal models. In this study, we present the development and characterization of a novel, reproducible, and cost-effective mouse model of cardiac dysfunction in African trypanosomiasis. We demonstrate that this model recapitulates major features of cardiac dysfunction in natural infection, including the presence of parasites in the cardiac interstitial spaces, alterations of cardiac biomarkers, and functional changes. This model represents a resource to support the understanding of cardiac complications of trypanosomiasis and the development of new therapies to prevent and treat cardiac involvement in African trypanosomiasis.